Electroacupuncture-based vagal stimulation attenuates epileptic seizures through a body–brain circuit - Yu Wang; Qingyang Zhang; Shuangshuang Wu; Keyu Hu; Siyi Bu; Yingjie Song; Fan Fei; Heming Cheng; Di Wu; Shuang Wang; Yi Guo; Cenglin Xu; et al. (Proceedings of the National Academy of Sciences, 2026)
Vagus nerve stimulation offers a promising strategy for seizure control but remains limited by its invasive delivery. Here, we reveal electroacupuncture (EA), an ancient neuromodulatory technique rooted in traditional Chinese medicine, at specific somatic acupoints linked to the vagal–brain axis to treat epilepsy and delineate the precise underlying neural mechanisms. We demonstrate that EA at the Dazhui (GV14) acupoint exhibits broad-spectrum antiseizure efficacy across multiple seizure models. Anatomical and functional analyses reveal that GV14 activates the vagal afferents and recruits neurons in the caudal nucleus of the solitary tract (cNTS), which are essential for seizure suppression. Using targeted recombination in active populations and chemogenetic manipulation, we show that GV14 EA suppresses seizures via the recruitment of a defined cNTS–locus coeruleus–amygdala circuit. Furthermore, through vagal afferent activity screening, we identify Yaoqi (EXB9) as an alternative therapeutic acupoint that activates a shared neural pathway to robustly attenuate seizures. Importantly, thread-embedding acupuncture at GV14 or EXB9 produces sustained seizure reduction in a chronic epilepsy model. Together, these findings elucidate a functional vagal–brain circuit underlying EA-induced seizure control and support its translational potential as a minimally invasive neuromodulatory strategy to replace vagal stimulation for epilepsy treatment.